Major and Trace Element Geochemistry of Bauxites of Ayranci, Karaman, Central Bolkardag, Turkey - Gurhan Yalcin, M.; Ilhan, Semiha (Asian Journal of Chemistry, 2012)
Central Bolkardag (Ayranci, Kucukkoras-Karaman) bauxites are one of the most important bauxite sources of the central Taurus zone. The aim of this study was to determine geological features and major and trace elements of Kucukkoras bauxites based on geochemical data from the bauxite deposits and rocks. To this aim, geochemical features of the region were investigated, a detailed map of the bauxite sites was drawn and chemical analyses of the collected specimens were made with inductively coupled plasma/mass spectrometry (ICP-MS). Kucukkoras diasporic bauxite deposits were located in Jurassicu-upper cretaceous aged uctepeler formation, were formed in the upper cretaceous period, extended in the NW-SE direction and were composed of three types of ores; i.e. lenses, karstic fills (sinkhole fills) and veins. Bauxites were found to have the following major oxides: SiO2 of 3.2005 %, Al2O3 of 57.7080 %, Fe2O3 of 23.365 %, MgO of 0.1035 %, CaO of 0.3290 %, Na2O of 0.0800 %, K2O of 0.0960 %, TiO2 of 3.1385 %, P2O5 of 0.0580 %, MnO of 0.1445 % and CrO3 of 0.5430 %. Based on the Al2O3/SiO2 ratio of bauxites, the mean module value was found to be 18.04, which indicates that Kucukkoras bauxites were the highest quality bauxites. Geochemical data showed that the bauxites were formed as a result of conversion of limestone into terra rossa and then conversion of terra rossa into bauxite.